The human experiment [videorecording (DVD)] - Nachman, Dana; Penn, Sean, 1960- (Kino Lorber, Inc., 2015)
Lifts the veil on the shocking reality that thousands of untested chemicals are in our everyday products, our homes and inside of us. Tells the personal stories of people who believe their lives have been affected by chemicals and takes viewers to the front lines as activists go head-to-head with the powerful and well-funded chemical industry.